Ready for advanced : - Norris, Roy (Macmillan, 2014)
A workbook pack that offers thorough consolidation of the grammar studies in the Student's Book. It provides students preparing for the CAE with extra writing practice, listening banks and exam practice. It also includes an a audio CD that contains all the audio needed, making it useful for revision and homework.